A New Monetary Era and the Necessity of Exchange Rate Policy Reformulation for Macroeconomic Performance: the Inclusive Nominal Exchange Rate (INEX). Lessons from Indonesia in ASEAN-10 - Moro, Kadjo Daniel Bitty; Mursinto, Dr. Djoko; Purwono, Dr. Rudi (Advances in Social Sciences Research Journal, 2016)
This paper is actually part of a research that was conducted in twenty five countries from the Association of Southeast Asian Nations (ASEAN-10) and the Economic Community of West African States (ECOWAS-15) about the factual correlation between exchange rate and five macroeconomic variables. However, here, we focus on the case of Indonesia, the largest economy of the regional integrated area ASEAN. The study starts from the fact that nowadays, because of the growing openness of national markets, no longer the interest rate but the exchange rate appears to be the single monetary tool that can be used to simultaneously boost economic growth and protect national economic fundamentals against adverse external shocks, but how? That question constitutes the major concern of this article. Using secondary macroeconomic data, this paper has adopted a mixed-methodology approach based on a correlation test and statistical mapping technique analysis which constitutes the novelty compared to previous studies on monetary issues. The paper reveals that Indonesia, under floating exchange rate regime has successfully controlled inflation rate but at the expense of the GDP growth. The major finding of this study is a proposal for new formulation of the exchange rate valuation named: the “Inclusive Nominal Exchange rate” (INEX) which is based on real economic performances of a country and the structure of its economy. An illustration of the INEX showed that in 2014, the macroeconomic fundamentals of Indonesia were better but, the nominal exchange rate failed to capture that performance.